POTENSI PEMANFAATAN DAUN SIRIH HUTAN DAN DAUN MIMBA UNTUK MENGENDALIKAN HAMA GUDANG KACANG TANAH DENGAN METODA BANTALAN KASA : LITERATURE REVIEW - Taufik Hidayat; Puput Novita; Febri Yandi; Saripah Ulpah (DINAMIKA PERTANIAN, 2021)
Application of synthetic chemical insectices is known to be the most effective approach in addressing infestation of insect pests. However, conventional insecticides are not appropriate to be applied against pests of stored food materials, such as peanut due to the residue issue. Method of fumigation which negate the residue issue is also not feasible for public practice due to the hazard potency. This consideration necessitates the exploration of safe insecticide material such as neem leaf and piper leaf using suitable method. Paper presented here is a literature review design to analyze related to the important pest of stored peanut, content and effication of neem and piper leaves, and the efficiency of muslin-cloth pad containing the botanicals. Based on the neem characteristics which is anteefedant and the characteristics of piper leaf which is volatile. It can be concluded that botanicals from these two species prepared in muslin-cloth pad, would be able to control pest of stored peanut.